Evaluating the intraoperative changes in several hemodynamic parameters using uscom method in severe burn patients undergoing burn necrotomy, skin grafting - Nguyen, Van Quynh; Vo, Van Hien (Tạp chí Y học Thảm hoạ và Bỏng, 2023)
Objective: To evaluate the intraoperative changes in some hemodynamic parameters by the USCOM method in severe burn patients undergoing burn necrotomy, skin grafting.Subjects and methods: 30 severe burn patients, aged 16-60, treated at the Emergency Department, National Burn Hospital, were scheduled for necrosis and skin grafting from May 2023 to December 2023. Cross-sectional, clinical descriptive study.Results: CO and CI values at all study times were within normal limits (3.5-8 l/min and 2.4-4.2 l/min/m2). CO and CI were highest at the time of pre-medication (6.93 and 4.24) and lowest at the time of skin grafting (5.87 and 3.61). SVR values at all times were within normal limits (800 - 1600 d.s.cm-5). SVR was highest at the time the patient was awake (1278.33) and lowest at the time immediately after induction of anesthesia (976.93). SVRI values at 3 times after induction of anesthesia, before necrotomy, and at the time of necrotomy were lower than normal values (1800-3200 d.s.cm-5.m2). SVI at the remaining time points was within normal limits. SV values at all times were within normal ranges (50-110 cm3). SVI values at most times were smaller than normal values (35 - 65 ml/m2), except for at the time of necrotomy (35.03). SVV values at all times were higher than normal (< 20%).Conclusion: Stroke volume variation (SVV) parameters at all study times were higher than normal values corresponding to the age range. The stroke volume index parameter SVI at most times was lower than the normal value, and SVRI at all times was not higher than the normal value. However, the parameters cardiac output (CO), cardiac index (CI), stroke volume (SV), and systemic vascular resistance (SVR) were all within the range of normal values corresponding to the age range at the research time points.